Cross-sectional observational study of nipple and areola changes during pubertal development and after menarche in 313 Italian girls - De Sanctis, Vincenzo; Elhakim, Ihab Zaki; Soliman, Ashraf T; Elsedfy, Heba; Soliman, Nada; Elalaily, Rania (Acta Biomedica Atenei Parmensis, 2016)
Obiective: To describe the characteristics of nipple development during puberty in Italian females. In addition this is compared with Tanner criteria for breast and pubic hair development at different stages and correlated with body mass index (BMI) and the menstrual age. Design: Cross-sectional observational study. Setting: Italian children and adolescents consecutively assessed at the Endocrine and Adolescent Outpatient Clinic of Private Accredited Quisisana Hospital of Ferrara. Partecipants: Healthy females 2-20 years, belonging to Italian middle socio-economic class. Study duration: This study was conducted for a total period of 39 months from September 2012 to December 2015. Methods: Demographic characteristics, age at menarche and menstrual duration, anthropometry (weight, height, BMI) and pubertal status (breast and pubic hair) were evaluated. The greatest diameters of the erect nipple and areola sizes were measured in all subjects in supine position using a plastic template with graduated circular cut-outs or a transparent graduated ruler. Results: Significant increments in nipple diameter were noted between Tanner’s stages B1, B2, B3, B4 and B5 but the differences between stages B1 vs B2, B3 vs B4, B4 were more significant (p<0.001) than the difference between B4 vs B5 (p<0.004).The same statistical pattern was documented between Tanner’s stage PH1 and PH2, PH2 and PH3 and PH4 and PH5. The nipple diameter increased significantly in relation to BMI in all Tanner’s stage groups (p: 0.021 for B1 vs B2; and p<0.001 for B3 vs B4 and B4 vs B5) but one (B2 vs B3=p: 0.518).A significant correlation was observed between duration of menses, nipple and areola sizes (r: 0.490; p=<0.001 and r: 0.252; p=0.012, respectively). Conclusions: The assessment of sexual maturation is important in population studies as well as for daily clinical encounter. In our subjects the mean age of onset of secondary sexual characteristics was 10.3±1.4 years and mean age at menarche was 12.02±1.5 years. The study provides the normative data for nipple and areola sizes in Italian girls. Change in nipple and areola sizes may represent an early marker for transition to puberty.